STUDI PENDAHULUAN FENOLOGI PEMBUNGAAN Eucalyptus pellita F. Muell DI WANAGAMA I, GUNUNGKIDUL,YOGYAKARTA (preliminary Phenological Study on Eucalyptus pellita F. Muell at Wanagama Educational Forest, Gunung Kidul, Yogyakarta) - , Yeni Widyana NR ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
Observation on the flowering phenology of Eucalyptus pellita was done in three-year and five-month old E. pellita plantations, at Wanagama Educational Forest, Gununglddul, Yogyakarta. The study was conducted to observe the flowering phenology of E. pellita and to estimate the value of reproductive success (RS). The developmental stages of E. pellita reproductive organ were detected by making the observation on (i) physical and morphological changes of reproductive organs, (ii) the developmental stages of reproductive organs, and (iii) the time and duration of each developmental stage. The estimation of reproductive success was done by randomly collecting 10 sample-trees. The value of RS was obtained from the percentage offruitlflower (ratio between the number ofrea1istic fruit and theoretic flower) times seedlovule (ratio between the number of viable seed and theoretical ovule). E. pe//ita spent 299 days to develop the reproductive organs, from the floral initiation to the ripening offruit and seed dispersal. Floral initiation began in January, peak flowering reached in March-April, and ripening offruit and seed dispersal occurred in September. From this f1l'streproductive cycle, the estimated value ofFr/F1 was 620/0, while that of S/O was 11%. The value ofRS was calculated to be 6.6%.